2020
DOI: 10.1002/joc.6674
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐model ensemble of CMIP6 projections for future extreme climate stress on wheat in the North China plain

Abstract: Future extreme climate events will become more intense and frequent with global warming, which is a great threat to wheat productivity in the North China Plain (NCP). Projecting future changes in extreme climate events is an important prerequisite for exploring crop adaptation measures to climate variation. In this study, we calculated 11 extreme climate indices at different wheat growth stages that are sensitive to wheat yield across NCP. The future climate projections were sourced from thirteen Global Climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Over 900 Mha land is impacted by salinity in the whole world (Rengasamy, 2006;Shiade and Boelt, 2020). Climate change such as extreme warming is expected to be more frequent in the future (Khan and Qaiser, 2006;Blackport and Screen, 2020;Bai et al, 2021). Such change could significantly affect seed germination (Walck et al, 2011;Mondoni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over 900 Mha land is impacted by salinity in the whole world (Rengasamy, 2006;Shiade and Boelt, 2020). Climate change such as extreme warming is expected to be more frequent in the future (Khan and Qaiser, 2006;Blackport and Screen, 2020;Bai et al, 2021). Such change could significantly affect seed germination (Walck et al, 2011;Mondoni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to warming climate, extreme climate events are anticipated to increase, which are likely to produce negative impacts on crop production (Porter and Semenov, 2005). When the crop phenology changes in the future are not considered, Bai et al (2020) noted that the frequency and intensity of heat extremes during wheat growing season were projected to increase over the 21st century for SSP245 and SSP585 scenarios, but those of cold extremes will decrease. In this study, the results showed that heat days around flowering had no significant change or a slight decrease for wheat under SSP245 and SSP585 scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed description of the method can be found in Liu and Zuo (2012). Bai et al (2020) assessed the performance of the downscaled GCMs data from CMIP6 in reproducing historical changes of extreme climate indices using the multi-model arithmetic mean and found that the ensemble results could better reproduce historical changes of extreme climate than any individual GCM. In this study, we downscaled climate inputs for APSIM model for the 1961-2100 period at the four agro-meteorological stations under each of the 20 GCMs for SSP245 and SSP585.…”
Section: Climate and Crop Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The region has a warm temperate monsoon climate with plenty of light and heat resources [37]. The mean annual temperature across the study area ranged from 9.6 to 16.0 • C in nearly fifty years [38]. The annual precipitation is not evenly distributed, with over 70% of precipitation appearing in July through September.…”
Section: Study Areamentioning
confidence: 99%